THE INFLUENCE OF LOCUS OF CONTROL, SELF-EFFICACY, AND ACCOUNTING ACHIEVEMENT LEARNING ON ACCOUNTING CAREER MATURITY OF THE TWELFTH GRADE STUDENTS OF THE ACCOUNTING PROGRAM IN PRIVATE VOCATIONAL HIGH SCHOOLS - Bahtiar, Mohammad Danang (International Journal of Education, 2017)
This study aimed to analyze the influence of locus of control, self-efficacy, and learning achievement in accounting on the career maturity of twelfth grade students of the accounting program in private vocational high schools. The population in the study were twelfth grade students of the Accounting Skills Program at SMK Wachid Hasyim, SMK Kartika 1, SMK and SMK Mahardhika Pawiyatan in the academic year 2015/2016 with a total sample of 175 students. Sampling was conducted using Proportional Sampling Systematic technique. This is descriptive research with quantitative approach, using multiple linear regression analysis. The results showed partially significant influence of the locus of control, self-efficacy, and learning achievements on career maturity of the accounting students, and a simultaneous influence of the locus of control, self-efficacy, and achievement of the twelfth grade students of the accounting Program in private vocational high schools.